Studies of China and Chineseness since the Cultural Revolution Volume 2: Micro intellectual history through de-central lenses - Clemente, Tina S.; Marwah, Reena 1960-; Shi, Zhiyu 1958-; Singh, Swaran 1961-; Tanigaki, Mariko 1960- (World Scientific, 2023)
"One reason why the influences of the Great Proletarian Cultural Revolution (roughly 1966-1976) in contemporary China have been so pervasive, profound, and long-lasting is that it challenged everyone to decide how she can and should be herself. Even scholars who study the Cultural Revolution from a presumably external vantage point must end up with an ideological position relative to whom they study. This amounts to a focused curiosity toward the Maoist agenda rivaling its alternatives. As a result, the political lives after the Cultural Revolution remain, ulteriorly and ironically, Maoist to a ubiquitous extent - how then can we cleanse, forget, neutralize, rediscover, contextualize, realign, revitalize, or renovate Maoism? All must appropriate ideologies for political and analytical purposes and adapt to how others use ideological discourses. The contexts of ideology are thus under constant reexamination for people to appreciate how they acquire their roles and duties. Those more practiced can even reversely give new meanings to reform, nationalism, foreign policy, or scholarship by shifting between Atheism, Maoism, Confucianism, and Marxism, incurring alternative ideological lenses to de-/legitimize their subject matter."--